Legal review on the online sale of homemade food and beverage products without a distribution permit from the National Agency of Drug and Food Control (BPOM) of the Republic Indonesia in relation to consumer protection in Medan City - Carlos Zefanya Sipayung; Marsella Marsella (Privietlab, 2025)
The objective of this research is to analyze the legal aspects concerning the online sale of homemade food and beverage products without distribution permits from the Indonesian National Agency of Drug and Food Control (BPOM), particularly in the city of Medan. This study employs a mixed legal research method, combining normative juridical and empirical approaches by reviewing relevant legislation and conducting interviews with small-scale business owners, BPOM officials, and representatives of the Medan Health Department. The findings indicate that the majority of homemade food and beverage entrepreneurs do not possess BPOM distribution permits due to a lack of understanding, limited financial resources, and the belief that such permits are unnecessary. Consequently, consumers are vulnerable to the safety of the products they consume. The state, through BPOM and local governments, must play an active role in providing both preventive and repressive legal protection, as well as in offering education and assistance to entrepreneurs to ensure the protection of consumer rights.